Konferencja Biskupów w świetle motu proprio "Apostolos suos" - Dyduch, Jan (Prawo Kanoniczne, 1998)
The Motu proprio: Apostolos Sttos of pope John Paul II,dated 21 May 1998, is a continuation and intensification of the Second Vatican Council's teaching on the Bishops Conferences. Bishops Conferences express the collegiality inthe Church, collegiality in the broader meaning; defined as „the spirit of collegiality” – affectus collegialis. This collegiality expresses bishops’ concern for the universal Church, but especially for the local Church, that is, the Church existing on the territory of one country and remaining under the Bishops Conference of that country. The sphere of activity of the Bishops Conference is regulated by the universal law and by its own statutes which must be approved by the Apostolic See. The Motu proprio: „Apostolos Suos” determines that the offices of a chairman and vice-chairman of the Bishops Conference are filled by an election. They are alected by all members from among the diocesan bishops. Besides its legislative and coordinative power, the Plenary Assembly of the Bishops Conference has the right to issue doctrinal declarations. Such declaration, made unanimously by the Conference, belongs to the authentic teaching of the Church and can be promulgated by its authority. If the declaration was supported by two thirds of the Conference's members (with the deliberative vote), then it requires the recognition of the Apostolic See.